The labilizing and stabilizing effect of physostigmine on CNS - Navrátil, J; Sklenovský, A; Camela, Z; Rypka, M (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1990)
The authors observed biphasic changes of dopamine, norepinephrine and serotonin in the rat brain stem after a single application of physostigmine (1 mg/kg of body weight). The results confirm the hypothesis of "labilization and stabilization" of membranes.
Keywords: Brain Stem; Physostigmine; Dopamine; mozkový kmen; mužské pohlaví; fysostigmin; krysa rodu Rattus; inbrední kmeny potkanů; Rats, Inbred Strains; Male; Norepinephrine; Serotonin; Animals; serotonin; Rats; zvířata; noradrenalin; dopamin